Biomarkers improving decisions making in clinical trials: explanations and examples - Faiha, Dhea Kirana; Lupitasari, Florentina Bety Indah; Fitria, Humairah; Salamah, Umi; Supriyati, Vidia Ajeng (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Biomarkers are originate from physiological processes, medical imaging, tissues, or chemicals. They are potentially useful indicators for every type of disease and have important roles on drug discovery and development, disease progression tracking, prognosis, diagnosis, and therapy response. Biomarkers provide precision measurement results, lower bias result, also faster early warning signal. Therefore, they can be used as a basis for clinical decisions. Biomarkers found in tissues, blood, and other bodily fluids. Depend on their purpose of usage, biomarkers can be categorized of diagnostic, prognostic to predicts disease progression, pharmacodynamic to measures the effect of a drug on a biological system, and predictive to predicts response to a specific treatment. In clinical trials, biomarker can be used as basic of decisions making. Therefore, several steps required to incorporate biomarkers in clinical trials are determine roles and functions of biomarkers, choose specific test and laboratory according to purpose of trial, describe test and protocol, carry out and report analysis validation appropriate for trial, implement test in trial, and plan sustainability of biomarker uses in future research. Biomarker have been used as basis of decision making in clinical trials in phase I-IV to recruit participants or making a decision whether the trial will be terminated or continued. In this review, we outlined general explanations about molecular biomarkers, step of biomarkers incorporation in clinical trial, and examples of several studies using molecular biomarkers in clinical trial as basis of decision-making.